Low pathogenic avian influenza virus isolates with different levels of defective genome segments vary in pathogenicity and transmission efficiency - Edyta Świętoń; Karolina Tarasiuk; Krzysztof Śmietanka (Veterinary Research, 2020)
Abstract Defective interfering particles (DIPs) of influenza virus are generated through incorporation of highly truncated forms of genome segments, mostly those coding polymerase complex proteins (PB2, PB1, PA). Such particles are able to replicate only in the presence of a virus with the complete genome, thus DIPs may alter the infection outcome by suppressing production of standard virus particles, but also by stimulating the immune response. In the present study we compared the clinical outcome, mortality and transmission in chickens and turkeys infected with the same infectious doses of H7N7 low pathogenic avian influenza virus containing different levels of defective gene segments (95/95(DVG-high) and 95/95(DVG-low)). No clinical signs, mortality or transmission were noted in SPF chickens inoculated with neither virus stock. Turkeys infected with 95/95(DVG-high) showed only slight clinical signs with no mortality, and the virus was transmitted only to birds in direct contact. In contrast, more severe disease, mortality and transmission to direct and indirect contact birds was observed in turkeys infected with 95/95(DVG-low). Apathy, lower water and food intake, respiratory system disorders and a total mortality of 60% were noted. Shedding patterns in contact turkeys indicated more efficient within- and between-host spread of the virus than in 95/95(DVG-high) group. Sequencing of virus genomes showed no mutations that could account for the observed differences in pathogenicity. The results suggest that the abundance of DIPs in the inoculum was the factor responsible for the mild course of infection and disrupted virus transmission.